P2X4 receptor controls microglia activation and favors remyelination in autoimmune encephalitis. Issue 8 (4th July 2018) - Zabala, Alazne; Vazquez‐Villoldo, Nuria; Rissiek, Björn; Gejo, Jon; Martin, Abraham; Palomino, Aitor; Perez‐Samartín, Alberto; Pulagam, Krishna R; Lukowiak, Marco; Capetillo‐Zarate, Estibaliz; Llop, Jordi; Magnus, Tim; et al.
Abstract: Microglia survey the brain microenvironment for signals of injury or infection and are essential for the initiation and resolution of pathogen‐ or tissue damage‐induced inflammation. Understanding the mechanism of microglia responses during pathology is hence vital to promote regenerative responses. Here, we analyzed the role of purinergic receptor P2X4 (P2X4R) in microglia/macrophages during autoimmune inflammation. Blockade of P2X4R signaling exacerbated clinical signs in the experimental autoimmune encephalomyelitis (EAE) model and also favored microglia activation to a pro‐inflammatory phenotype and inhibited myelin phagocytosis. Moreover, P2X4R blockade in microglia halted oligodendrocyte differentiation in vitro and remyelination after lysolecithin‐induced demyelination. Conversely, potentiation of P2X4R signaling by the allosteric modulator ivermectin (IVM) favored a switch in microglia to an anti‐inflammatory phenotype, potentiated myelin phagocytosis, promoted the remyelination response, and ameliorated clinical signs of EAE. Our results provide evidence that P2X4Rs modulate microglia/macrophage inflammatory responses and identify IVM as a potential candidate among currently used drugs to promote the repair of myelin damage. Synopsis: Innate immune cells contribute to axonal damage and demyelination in multiple sclerosis (MS) but they are also pivotal in promoting repair responses. Modulating microglia/macrophage P2X4R activation determines clinical outcome in the experimental autoimmune encephalomyelitis (EAE) model of MS. Expression of P2x4r and the two transcription factors controlling its expression, Irf8 and Irf5, was increased in EAE. EAE clinical symptoms were exacerbated by P2X4R blockage and ameliorated by P2X4R potentiation with the allosteric modulator ivermectin. P2X4R blockage does not interfere with the immune priming or with blood‐brain‐barrier permeability during the acute phase of EAE. P2X4R activation favors a switch of microglia/macrophage to an anti‐inflammatory phenotype and increases BDNF release, that promotes oligodendrocyte differentiation. P2X4R activation increases myelin phagocytosis and degradation at lysosomes, thus indirectly promoting remyelinating responses. Abstract : Innate immune cells contribute to axonal damage and demyelination in multiple sclerosis (MS) but they are also pivotal in promoting repair responses. Modulating microglia/macrophage P2X4R activation determines clinical outcome in the experimental autoimmune encephalomyelitis (EAE) model of MS.